Behavior associated with the handling of sanitizers (Research, Society and Development, 2021)
This study aimed to evaluate behaviors associated with handling of sanitizers in a largely low-income neighborhood located in Itu – SP, Brazil. This work was carried out based upon application of a semi-structured, individual and closed questionnaire to 100 inhabitants of Parque São Camilo aged 30 or older. The extent of the associations between the assessed factors was determined by Fisher exact and these were considered significant when p